Managing Stakeholders in Elementary Schools: Leadership Practices for Effective School Operations in Zambales - Marie Fe D. de Guzman; Rene C. Dizon, Jr.; Raymond D. Espiritu (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study explored the leadership practices of elementary school leaders in managing stakeholders within public schools in Zambales, Philippines, with the aim of improving school operations and fostering a collaborative and inclusive educational environment. The research focused on leadership dimensions such as communication, engagement, relationship-building, and conflict resolution, considering the perspectives of both school leaders and teachers. Given the challenges in rural areas, including mismanagement of resources and low levels of stakeholder involvement, the study emphasized the crucial role of school leadership in overcoming these barriers. Using a descriptive quantitative research design, data were collected from 30 principals and 535 teachers from 15 public elementary schools. The results indicated that both leaders and teachers placed a high value on relationship-building, particularly through recognizing stakeholder contributions and maintaining consistent communication. Teachers highlighted the importance of active participation in decision-making processes, while principals emphasized proactive problem-solving and relationship development. The study also revealed that demographic variables, including age, gender, and educational qualifications, influenced the perceptions of leadership practices. Based on these findings, an intervention plan was proposed to enhance leadership practices in communication, engagement, and conflict resolution through targeted training. The anticipated outcomes of the intervention included improved stakeholder communication, increased teacher involvement in decision-making, strengthened relationships within the school community, and enhanced conflict resolution practices. Ultimately, the study aimed to create a more cooperative school environment, leading to improved school performance and better academic outcomes for students.